Hadith #2714 - Sunan Abi Dawud - al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
Salih bin Muhammad said “We went out on an expedition with Al Walid bin Hisham and Salim bin ‘Abd Allaah bin ‘Umat and ‘Umar bin ‘Abd Al Aziz were with us. A man had been dishonest about booty. Al Walid ordered to burn his property and it was circulated (among the people). He did not give him his share. Abu Dawud said “This is sounder of the two traditions. Others narrated that Al Walid bin Hashim burnt the Camel saddle of Ziyad bin Sa’d “He had been dishonest about booty and he
Grade: Da'if

Hadith #2931 - Sunan Abi Dawud - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Musa bin 'Amir bin Amarh موسى بن عامر بن عمارة بن خريم; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The Prophet (ﷺ) appointed Ubn Umm Makthum as a governor of Medina (in his absence) twice.
Grade: Sahih

Hadith #4307 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Umama bin Sahl; Musa bin Jbyr al-Madni Mwla موسى بن جبير المدني; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The people will establish cities, Anas, and one of them will be called al-Basrah or al-Busayrah. If you should pass by it or enter it, avoid its salt-marshes, its Kall, its market, and the gate of its commanders, and keep to its environs, for the earth will swallow some people up, pelting rain will fall and earthquakes will take place in it, and there will be people who will spend the night in it and become apes and swine in the morning.
Grade: Sahih

Hadith #4831 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Anas b. Malik from the Prophet (ﷺ) through a different chain of narrators in a similar way.
Grade: Sahih